Sime Darby Property - Abdul Razak, Amierul Hasiefdad; Abdul Razak, Putra Muhammad Adam Shafiq; Mat Jusoh, Siti Nur Athia Wahidah (2024)
Two powerful brands in the industry have partnered to become Sime Darby Brunsfield. The Brunsfield Group, a highly regarded technology-based developer for construction, information, and communications that has set numerous records, has partnered with the Sime Darby Group, an established leading multinational corporation and one of Southeast Asia's largest conglomerates. Through a strategic agreement, the Sime Darby Brunsfield initiative will combine the various assets and resources of both parties and make use of their distinct skills, knowledge, and experiences. With this strategic cooperation, they want to produce higher quality and significantly increase value for all of their major stakeholders while also creating actual synergy.A joint venture partnership between Sime UEP Properties Bhd and Brunsfield Group has begun construction on Subang Avenue, a project in Subang Jaya that will include serviced apartments and a 250,000-square-foot upscale retail space. Among the other projects is the highly acclaimed Oasis Square development, which was finished in 2009.